Pengaruh Digital Marketing, Affiliate Marketing, Fear of Missing Out (FoMO), dan Online Customer Review Terhadap Keputusan Pembelian Skincare Facetology Pada Platform TikTok Shop ( Studi Kasus Pada Generasi Z di Kota Malang ) - Putri, Alkansha Berlina Eka; Arifin, Rois; Amin, Muh Sirojuddin (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of digital marketing, affiliate marketing, fear of missing out (FoMO) and online customer reviews on purchasing decisions for facetology products on the tiktokshop platform (case study of generation z in Malang). The population used in this study is generation z in the city of Malang who buy facetology products on the tiktokshop platform. The sample in this study was 105 people obtained using the Maholtra formula. The variables used in this study are purchasing decisions as the dependent variable, while digital marketing, affiliate marketing, fear of missing out, and online customer reviews as independent variables. The results of this study concluded that digital marketing, affiliate marketing, fear of missing out, and online customer reviews simultaneously influence purchasing decisions, while the fear of missing out variable does not have a significant effect on purchasing decisions. Keywords: Purchasing Ecisions, Digital Marketing, Affiliate Marketing, Fear Of Missing Out, Online Customer Review